ERBB2 mutation frequency in lobular breast cancer with pleomorphic histology or high‐risk characteristics by molecular expression profiling. Issue 3 (7th January 2019) - Christgen, Matthias; Bartels, Stephan; Radner, Martin; Raap, Mieke; Rieger, Luisa; Christgen, Henriette; Gluz, Oleg; Nitz, Ulrike; Harbeck, Nadia; Lehmann, Ulrich; Kreipe, Hans
Abstract : HER2‐positive breast cancer is defined by amplification or overexpression of the HER2/ERBB2 oncogene and accounts for about 15% of breast cancer cases. Somatic mutation of ERBB2 is an alternative mechanism, by which activation of HER2 signaling can occur. ERBB2 mutation has been associated with invasive lobular breast cancer (ILBC). This study investigates the frequency and phenotype of ILBC harboring mutated ERBB2 . The ERBB2 mutation status was determined by next generation sequencing and/or pyrosequencing in n = 106 ILBCs, including n = 86 primary or locally recurrent tumors and n = 20 metastases from visceral organs, soft tissue, or skin. Immunohistochemical characteristics were determined using tissue microarrays. This series was enriched for ILBCs with pleomorphic histology and/or high‐risk expression profiles (Oncotype DX, recurrence score RS > 25). Nearly all specimens were E‐cadherin‐negative (99%), estrogen receptor (ER)‐positive (92%), and lacked ERBB2 overexpression (96%). ERBB2 mutations (p.V777L, p.L755S, p.S310F) were identified in 5/106 (5%) cases. ERBB2 ‐mutated cases included 2/86 (2%) primary tumors and 3/20 (15%) metastases ( P = 0.045). ERBB2 ‐mutated cases were associated with loss of ER (2/7, 29%, P = 0.035) and histological grade 3 (4/34, 12%, P = 0.023), but not with solid growth (3/31, 10%, P = 0.148) or pleomorphic histology (2/27, 7%, P = 0.599). No ERBB2 mutation was detected in ILBCs with RS > 25 (0/22, 0%). In 10 patients with multiple matched specimens ( n = 25), the ERBB2 mutational status was always concordant. In summary, a small subset of ILBCs harbors potentially actionable ERBB2 mutations. In ERBB2 ‐mutated ILBCs, no association with pleomorphic histology was found.